Transcriptome analysis reveals the genetic basis underlying the formation and seasonal changes of nuptial pads in Rana chensinensis - Fuyuan Qiu; Qingbo Ai; Jun Li; Hua Wu (BMC Genomics)
Abstract Background Nuptial pads, a typical sexually dimorphic trait in anurans, are located on the first digit of the male forelimb in Rana chensinensis and exhibit morphological changes synchronized with breeding cycles. However, the genetic mechanisms underlying its formation and seasonal changes remain poorly understood. Results To identify genes and biological processes associated with the development and seasonal variations of nuptial pads, we conducted a comprehensive transcriptome analysis on nuptial pads and hind toe skin across both sexes at different breeding periods in R. chensinensis. We identified numerous sexually and seasonally differential expression genes in nuptial pads. Notably, genes including KRT, TRY, HPDB, AKR1C1, and AKR1C3 were identified as potential key regulators of keratinization and coloration variation in nuptial pads. We further examined gene co-expression modules closely linked to nuptial pad development. These modules contained genes involved in signal transduction, substance transport, cytoskeletal structure, energy metabolism, and protein modification, suggesting that the development of nuptial pads is a complex multifaceted regulatory process. Furthermore, genes in modules associated with pad development during the breeding season were primarily involved in apoptosis, steroid hormone synthesis, autophagy, and cytochrome P450 pathways, suggesting their pivotal role in pad formation. Additionally, key regulators of the cell cycle, such as FOXO4, PIK3C2A, and GSPT2, were implicated in influencing nuptial pad development by modulating cell differentiation and proliferation. Conclusions Our study provides a valuable reference for investigating the molecular basis of sexual dimorphism in R. chensinensis and other amphibian species more broadly.